Physicochemical Interaction of ZnO Fine Particles with 5‐Mono‐(4‐carboxyphenyl)‐10, 15, 20‐Triphenylporphyrin. Issue 10 (18th September 2015) - Khan, Abbas; Zada, Amir; Humayun, Muhammad
Abstract This study deals with an investigation on the preparation and physicochemical interactions of ZnO nanoparticles with acid functionalized porphyrin [5‐mono‐(4‐carboxyphenyl)‐10, 15, 20‐triphenylporphyrin (CPTPP)] for photovoltaic applications in a detailed manner. Zinc acetate and sodium hydroxide were used as the starting materials for the synthesis of ZnO nanoparticles at 60 °C in an alcoholic medium. The freshly prepared fine particles were then functionalized with CPTPP. Both the virgin and pregnant ZnO particles were characterized by using UV‐Visible spectrophotometry (UV), fluorescence emission (PL), Fourier transform infrared spectroscopy (FTIR), X‐ray diffraction (XRD) and scanning electron microscopy (SEM). The band gap energy obtained for ZnO particles, having a value of 3.47 eV, shows significant quantum confinement effect and enhanced photophysical activity. FTIR analysis of the doped ZnO nanostructures showed the presences of some chemical species. SEM analysis revealed a clear change in the surface morphologies of undoped ZnO. The average crystallite size of nanoparticles, calculated from XRD peaks, was found in the nano regime. The lattice parameters calculated for ZnO nanocrystals were also found in good agreement with those given in the literature. From the enhancement in the red shift of the UV‐Vis spectra, it is concluded that hybridization of acid functionalized porphyrin can cause a significant expansion in the total absorption region of ZnO semiconductor for photovoltaic applications.